STRATEGY BUMDESA (VILLAGE-OWNED ENTERPRISE) IN THE TOURISM DEVELOPMENT VILLAGE OF TAMAN PINGGIR GAWAN (TPG), PILANGGEDE VILLAGE, BALEN DISTRICT, BOJONEGORO REGENCY - Ayu Anggita Sari; Lukman Arif (DIA: Jurnal Administrasi Publik, 2021)
Pilanggede Village is one of the villages that has a village economic institution called BUMDesa Pilanggede Gemilang. Which BUMDesa has succeeded in building a tourist village destination. The development of this tourist village is named the Taman Pinggir Gawan Tourism Village (TPG) which presents a characteristic of the panoramic beauty of the Bengawan Solo River. However, behind the panoramic beauty, the Bengawa Solo River is a river that is prone to flood disasters when the rainy season arrives. So that BUMDesa Pilanggede makes efforts to minimize the impact of disasters and also to maintain the existence of tourist villages. This research aims to examine how the BUMDesa strategy is in the development of the TPG tourism village, Pilanggede Village, Balen District, Bojonegoro Regency. The research method used is descriptive qualitative by describing the facts that occur in the field. Data collection techniques using observation, interviews, documentation, and triangulation. The results showed that in the process of developing a tourist village, several programs had been designed. The program includes establishing the image of tourism with the addition of new vehicles and also improving facilities and infrastructure, improving the quality of human resources through training, carrying out activities to maintain environmental hygiene, and also promoting through social media.